An Alu element retroposition in two families with Huntington disease defines a new active Alu subfamily. - Hutchinson, G B (1993)
Alu repetitive elements represent the most common short interspersed elements (SINEs) found in primates, with an estimated 500,000 members in the haploid human genome. Considerable evidence has accumulated that these elements have dispersed in the genome by active transcription followed by retroposition, and that this process is ongoing. Sequence variation between the individual elements has lead to the hierarchical classification of Alu repeats into families and subfamilies. Young subfamilies that are still being actively transposed are of considerable interest, and the identification of one such subfamily (designated 'PV') has lead to the hypothesis that the most recent retroposition events are due to a single master Alu source gene. In the course of our search for the gene causing Huntington disease, we have detected an Alu retroposition event in two families. Sequence analysis demonstrates that this Alu element is not a member of the PV subfamily, but is similar to 5 other Alu elements in the GenBank database. Together, these Alu elements, all of which contain a 7 base-pair internal duplication, define a distinct subfamily, designated as the Sb2 subfamily, providing evidence for a second actively retroposing Alu source gene. These data provide support for multiple source genes for Alu retroposition in the human genome.